Effectiveness and Pedagogical Approaches in Technology-Enhanced Internet Ethics Education for Elementary Students: A Systematic Review - Zahroh, Fatimatus; Purwoko, Budi; Ummah, Fiena Saadatul (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
This systematic review examines technology-enhanced pedagogical approaches in internet ethics education and their effectiveness in promoting safe online behavior among elementary school students within the context of increasing digitalization in education. Following the PRISMA guidelines, 15 peer-reviewed studies published between 2020 and 2025 were systematically identified, selected, and analyzed. The review focuses on various instructional strategies supported by digital technologies, including digital game-based learning, interactive learning programs, privacy literacy training, and collaborative school–parent interventions. The findings indicate that technology-mediated pedagogical approaches positively contribute to students’ digital literacy, ethical awareness, and self-efficacy in navigating online environments. In particular, game-based and interactive digital learning environments demonstrate strong potential in enhancing student engagement and facilitating the understanding of abstract ethical concepts. However, the review also reveals a persistent gap between knowledge acquisition and actual behavioral change. In addition, several methodological limitations were identified, including small sample sizes, short intervention durations, and limited cross-cultural generalizability. The results suggest that the effectiveness of internet ethics education depends largely on how digital technologies are meaningfully integrated into pedagogical design rather than used merely as instructional tools. A hybrid instructional approach that combines technology-enhanced learning with offline reinforcement and multi-stakeholder collaboration appears to offer more sustainable outcomes. This study contributes to the field of technology-enhanced pedagogy by synthesizing current evidence on the role of digital tools in shaping ethical learning and safe online behavior among young learners, while also identifying directions for future research.